Children as Victims of Forced Marriages in Lesotho: A Question of Cultural Practice or Approval of Child Exploitation - Mosa Likoti, Precious; Kevin Sibanyoni, Ephraim (International Journal of Criminology and Sociology, 2022)
This study focuses on the experiences of children as victims of abduction into forced child marriage in Lesotho. The study pays attention to children living in the rural area of Semonkong, where patterns of abduction into forced marriage are common. The objectives were, to explore factors that contribute to incidents of a child forced marriages, to determine the effects of a child forced into marriages. The study used a qualitative research method. A sample of 10 participants (all women aged 21-51) from the Semonkong area in Lesotho were sampled using Snowball sampling. In-depth interviews were used to collect data and were analyzed thematically. The findings: families use cultural practice as a means to exact power and authority to exploit children to escape poverty. Most girls were abducted without their consent, threatened, and were continuously violated in their marriages. They experienced damaging and degrading psychological effects from abduction but more so in their marriages. They endure all sorts of abuse and never reported the incident to the police. Recommendations: Preventing forced child marriage requires strengthened legal and policy frameworks, to ensure increased awareness and greater enforcement of existing laws.